Edge-thionic acid-functionalized graphene nanoplatelets as anode materials for high-rate lithium ion batteries. (August 2019) - Fan, Qinghua; Noh, Hyuk-Jun; Wei, Zengxi; Zhang, Jiakui; Lian, Xin; Ma, Jianmin; Jung, Sun-Min; Jeon, In-Yup; Xu, Jiantie; Baek, Jong-Beom
Abstract: Although lithium ion batteries (LIBs) hold great promise as a next generation power supply, the poor rate capability of the graphite that is mainly used as the battery anode limits high-performance LIBs. Compared to other reported carbon-based materials, however, its relatively low average working voltage still makes it attractive. Herein, we were able to introduce carbon disulfide (CS2 ) at the edges of graphene nanoplatelets (GnPs) with rich –C=S/-C-S bonds via ball-milling graphite in the presence of CS2 . The resultant edge-thionic acid-functionalized GnPs (TAGnPs) exhibited a larger accessible surface area and smaller particle size than pristine graphite. Importantly, the TAGnPs retained a long-range-ordered layered structure similar to pristine graphite. When the TAGnPs were used as anode materials for LIBs, they displayed superior rate capability ( e.g., high average reversible capacities of 228.3, 208.1, 141.0 and 80.6 mAh g −1 at 0.5, 1, 2 and 5 A g −1, respectively) compared to pristine graphite and the reference edge-hydrogenated GnPs (HGnPs), which mainly have -C-H bonds at their edges. Theoretical calculations also indicated that the presence of –C=S/-C-S bonds at the edges of TAGnPs enabled stronger Li + adsorption capability. Graphical abstract: Image 1 Highlights: Edge-thioated graphene nanoplatelets (TAGnPs) prepared by ball-milling graphite in the presence of carbon disulfide (CS2 ). TAGnPs have long-range-ordered structure similar to graphite. The TAGnPs have a larger accessible surface area than graphite. TAGnPs exhibit superior rate capability (>0.5 A g −1 ). TAGnPs reveal high average reversible capacities of 228.3, 208.1, 141.0 and 80.6 mAh g −1 .